AUDITOR KOMPETENSI DI INSPEKTORAT DAERAH PROVINSI SULAWESI SELATAN KOMPETENSI AUDITOR DI INSPEKTORAT DAERAH PROVINSI SULAWESI SELATAN - Mansyur, Shinta Rahmi; Imbaruddin, Amir; Rasdiyanti, Andi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Auditor competencies in regional inspectorates encompass the ability to conduct audits, evaluations, and controls on financial management and public policies, ensuring accountability and transparency. The purpose of this article is to analyze auditor competencies in improving the effectiveness of supervision in the Regional Inspectorate of South Sulawesi Province. The research method employed in this study is a qualitative approach, utilizing a case study design. The qualitative method was chosen because this study aims to explore the meaning, experiences, and perceptions of officials in the Regional Inspectorate of South Sulawesi Province. The results of the study indicate that. Developing auditors' technical skills is key to improving the effectiveness of regional financial and budget oversight. Technical skills encompassing internal audit, government accounting, data analysis, information technology, and regulatory knowledge have proven crucial and can be developed through formal training and continuing education. The Regional Inspectorate's commitment to developing its auditors' competencies through various internal training programs, seminars, workshops, and mentoring demonstrates a positive step toward improving the quality of oversight. Officials and expert auditors emphasized the importance of integrating technical and non-technical skills in addressing the challenges of digitalization and the complexity of regional government financial management. By continuing to strengthen auditor capacity through a comprehensive and sustainable development approach, the South Sulawesi Provincial Inspectorate is optimistic about improving accountability, transparency, and efficiency in regional financial management, thereby contributing positively to better governance in the future. ABSTRAKKompetensi auditor di inspektorat daerah mencakup kemampuan untuk melakukan pemeriksaan, evaluasi, dan pengendalian terhadap pengelolaan keuangan serta kebijakan publik guna memastikan akuntabilitas dan transparansi. tujuan dari artikel ini adalah, untuk menganalisis kompetensi auditor terhadap peningkatan efektivitas pengawasan di Inspektorat Daerah Provinsi Sulawesi Selatan. Metode penelitian yang digunakan dalam studi ini adalah metode kualitatif, dengan pendekatan studi kasus. Metode kualitatif dipilih karena penelitian ini bertujuan untuk menggali makna, pengalaman, dan persepsi aparatur di Inspektorat Daerah Provinsi Sulawesi Selatan. Hasil penelitian menunjukkan bahwa; pengembangan keterampilan teknis auditor merupakan kunci utama dalam meningkatkan efektivitas pengawasan keuangan dan anggaran daerah. Keterampilan teknis yang mencakup audit internal, akuntansi pemerintahan, analisis data, teknologi informasi, dan pengetahuan regulasi terbukti sangat penting dan dapat dikembangkan melalui pelatihan formal serta pendidikan berkelanjutan. Komitmen Inspektorat Daerah dalam mengembangkan kompetensi auditornya melalui berbagai program pelatihan internal, seminar, lokakarya, dan pembimbingan menunjukkan langkah positif menuju peningkatan kualitas pengawasan. Para pejabat dan auditor ahli menekankan pentingnya integrasi antara keterampilan teknis dan non-teknis dalam menghadapi tantangan digitalisasi dan kompleksitas pengelolaan keuangan pemerintah daerah. Dengan terus memperkuat kapasitas auditor melalui pendekatan pengembangan yang komprehensif dan berkelanjutan, Inspektorat Daerah Provinsi Sulawesi Selatan optimis dapat meningkatkan akuntabilitas, transparansi, dan efisiensi pengelolaan keuangan daerah, sehingga berkontribusi positif terhadap tata kelola pemerintahan yang lebih baik di masa mendatang.